2018
DOI: 10.1111/his.13629
|View full text |Cite
|
Sign up to set email alerts
|

High‐grade PanIN presenting with localised stricture of the main pancreatic duct: A clinicopathological and molecular study of 10 cases suggests a clue for the early detection of pancreatic cancer

Abstract: Isolated high-grade PanIN may present with pancreatic duct stenosis. Therefore, intensive investigations including pancreatic juice cytology will be required for patients with unexplained pancreatic duct stenosis. The abnormal expression of p53 and SMAD4 is infrequent, while GNAS may be mutated in premalignant lesions mainly affecting the main pancreatic duct, similar to KRAS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 23 publications
1
50
0
Order By: Relevance
“…Previous studies have reported similar findings in other pancreatic precursor lesions, such as PanINs and IPMNs, using next‐generation sequencing or droplet digital PCR. Together, these studies also support the heterogeneity in the tumorigenesis of pancreatic precursor lesions …”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Previous studies have reported similar findings in other pancreatic precursor lesions, such as PanINs and IPMNs, using next‐generation sequencing or droplet digital PCR. Together, these studies also support the heterogeneity in the tumorigenesis of pancreatic precursor lesions …”
Section: Discussionsupporting
confidence: 66%
“…The other KRAS gene included the wild‐type gene in all normal cases (G12R, G12C, G12A, and G12V). Allowing a mean + 3 standard deviations, the percentage of each type of KRAS mutation in MCN was normalised on thresholds of 1.1% for G12R, 0.22% for G12D, 0.25% for G13D, and 0% for others, based on previous studies …”
Section: Methodsmentioning
confidence: 99%
“…Although imaging suggested a solid mass lesion, no discrete nodule was identified histologically. In addition, various conditions such as small cancers, neuroendocrine tumors, or even pancreatic intraepithelial neoplasia that potentially obstruct the duct system were not identified in this case. The single abnormality observed in the adjacent pancreas was pancreatitis with neutrophilic epithelial injury reminiscent of GELs observed in type 2 AIP.…”
Section: Discussionmentioning
confidence: 81%
“…Until now it was thought that PanINs frequently display abnormal p53 expression and loss of SMAD4/DPC4 expression [22,23]. However, recent studies with isolated high-grade PanINs demonstrate that aberrant p53 expression occurs only in 20% of high-grade PanINs and all high-grade PanINs show intact SMAD4/DPC4 expression [24,25]. These discrepancies in previous studies may have been due to the presence of intraductal spread of invasive ductal adenocarcinomas.…”
Section: Paninmentioning
confidence: 99%
“…Intraductal spread, also known as intraductal cancerization, is observed in up to 70% of surgically resected PDACs [27], and is extremely difficult to differentiate from high-grade PanIN on hematoxylin and eosin-stained slides [5]. Loss of SMAD4/DPC4 expression can be a differentiating feature of intraductal spread of invasive PDAC, while high-grade PanIN shows intact SMAD4/DPC4 expression [24,25]. …”
Section: Paninmentioning
confidence: 99%